2013
DOI: 10.1177/1535370213493718
|View full text |Cite
|
Sign up to set email alerts
|

Emu oil expedites small intestinal repair following 5-fluorouracil-induced mucositis in rats

Abstract: Mucositis resulting from cancer chemotherapy is characterized by intestinal inflammation and ulceration. Previously, emu oil (EO) improved intestinal architecture (Br J Nutr, 2010) in a rat model of chemotherapy-induced mucositis. We investigated EO for its further potential to promote intestinal repair in this mucositis model. Female Dark Agouti rats (n = 8/group) were gavaged with water, olive oil (OO) or EO once daily (1 mL), injected with 5-fluorouracil (5-FU) or saline on day 5 and euthanized on day 8, 9,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
61
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 48 publications
13
61
0
Order By: Relevance
“…This assessment revealed that some amount of MPO exists in normal tissue, as MPO is an enzyme present in neutrophils. 16,17 Several previous studies have also shown that some level of MPO exists in normal tissue. 19,20 Therefore, we conclude that it may be possible to reduce the severity of oral mucositis if the MPO levels in the irradiated tissues are maintained at low concentrations.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…This assessment revealed that some amount of MPO exists in normal tissue, as MPO is an enzyme present in neutrophils. 16,17 Several previous studies have also shown that some level of MPO exists in normal tissue. 19,20 Therefore, we conclude that it may be possible to reduce the severity of oral mucositis if the MPO levels in the irradiated tissues are maintained at low concentrations.…”
Section: Discussionmentioning
confidence: 94%
“…On days 7, 10, and 13 after irradiation, the degree of oral mucositis of the lingual dorsum in each rat was evaluated using a grading scale employed in previous experiments. 15,16 The bars represent the mean AE standard error of the mean (SEM). The data were analyzed using an analysis of variance (ANOVA) and Tukey's test.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant decrease in activated neutrophil infiltration, improvement in crypt depth and villus height, decrease in acute inflammation and overall improvement in mucosal architecture in the intestine have been reported after Emu oil supplementation (84,85). Lyprinol, a lipid extract derived from mussels and rich in omega-3 polyunsaturated fatty acids partially improved 5-FU induced GIM in rat models (86).…”
Section: Miscellaneous Complementary Therapiesmentioning
confidence: 99%
“…Although 5-FU significantly increased MPO levels (≥ 307%; P < 0.001) in all intestinal regions, compared to healthy controls, LDR significantly decreased ileal MPO activity (45%; P < 0.05) in 5-FU treated rats, compared to 5-FU controls; indicating a reduction of acute inflammation in the distal small intestine. (Mashtoub, 2013). However, the effects of Ostrich Oil (OO) remain unexplored.…”
Section: Methodsmentioning
confidence: 99%